Early Jurassic adakitic rocks in the southern Lhasa sub-terrane, southern Tibet: petrogenesis and geodynamic implications - Shui, Xinfang; He, Zhenyu; Klemd, Reiner; Zhang, Zeming; Lu, Tianyu; Yan, Lili (Geological Magazine, 2018)
Cretaceous–Miocene adakitic rocks in the southern Lhasa sub-terrane have been intensively investigated, while possible Early Jurassic adakitic rocks in this area have been largely neglected. Petrological and geochemical studies revealed adakitic affinities of an Early Jurassic quartz diorite intrusion with mafic enclaves and three tonalite bodies from the Jiacha area in the southern Lhasa sub-terrane. Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) zircon U–Pb dating suggests crystallization ages of 199–179 Ma for these rocks. Both quartz diorites and tonalites have typical adakitic geochemical characteristics such as high Al2O3 (15.14–18.22 wt.%) and Sr (363–530 ppm) contents, low Y (4.46–15.9 ppm) and Yb (0.51–1.74 ppm) contents and high Sr/Y ratios of 27–106. The adakitic quartz diorites are further characterized by high MgO (2.63–3.46 wt.%), Mg# (48–54) and ε Hf(t) (6.6–13.4) values, which were probably produced by partial melting of a subducted oceanic slab with a mantle contribution. The adakitic tonalites have very low abundances of compatible elements and relatively low ε Hf(t) values (3.5–10.3), and are interpreted to have formed by partial melting of Neoproterozoic mafic lower crust. Upwelling asthenosphere, triggered by rollback of the subducting Bangong–Nujiang (Meso-Tethys) oceanic plate, provided the necessary heat for slab and lower crust melting, resulting in the geochemical diversity of the coexisting felsic intrusive rocks. Contrary to other models, this study further demonstrates that the Bangong–Nujiang oceanic plate was subducted southward beneath the Lhasa terrane during the Early Jurassic.
Keywords: Adakitic rocks; slab melting; Early Jurassic; Bangong-Nujiang (Meso-Tethys) Ocean; southern Lhasa sub-terrane

Identifying crystal accumulation and melt extraction during formation of high-silica granite - Lu, Tianyu; He, Zhen-Yu; Klemd, Reiner (Geology, 2022)
High-silica (>70 wt% SiO2) magmas are usually believed to form via shallow crustal-level fractional crystallization of intermediate magmas. However, the broad applicability of this model is controversial, because the required crystal-melt separation processes have rarely been documented globally up to now. The ca. 50 Ma Nyemo composite pluton of the Gangdese batholith belt in southern Tibet, which comprises intrusive rocks with intermediate-to high-silica compositions (65-78 wt%), offers a unique opportunity for substantiating the coexistence of extracted melts and complementary silicic cumulates in one of Earth's most complete transcrustal silicic magmatic systems. The Nyemo pluton intrusive rocks exhibit similar zircon Hf isotopic compositional ranges (mean epsilon(Hf(t)) = +5.7 to +8.3), suggesting a common, non-radiogenic magma source with crustal assimilation in the deep crust. Yet, these rocks have distinct geochemical characteristics. High-silica miarolitic and rapakivi granites are strongly depleted in Ba, Sr, and Eu, and their zircon trace elements show extremely low Eu/Eu* and Dy/Yb. In contrast, monzogranite is relatively enriched in Ba and Sr with minor Eu anomalies, and the zircon trace elements are characterized by relatively high Eu/Eu* and Dy/Yb. Therefore, we propose that the high-silica granites represent highly fractionated melt extracted from a mush reservoir at unusually low storage pressure (similar to 99-119 MPa), and that the monzogranite constitutes the complementary residual silicic cumulates.
CRIS-Team WoS Importer:2022-02-11

Mesoproterozoic juvenile crust in microcontinents of the Central Asian Orogenic Belt: evidence from oxygen and hafnium isotopes in zircon - He, Zhenyu; Klemd, Reiner; Yan, Li-Li; Lu, Tianyu; Zhang, Zeming (Scientific Reports, 2018)
We report in situ O and Hf isotope data of zircon grains from coeval Mesoproterozoic (ca. 1.4 Ga) igneous metamafic (amphibolite) and granitic rocks of the Chinese Central Tianshan microcontinent (CTM) in the southern Central Asian Orogenic Belt (CAOB). Zircon grains from amphibolite have mantle-like δ18OVSMOW values of 4.7–5.6‰ and juvenile Hf isotopic compositions (εHf(t) = 8.4–15.3; TDMC = 1.57–1.22 Ga), whereas those from granitic rocks have δ18OVSMOW values of 5.6–7.0‰ and evolved Hf isotopic compositions (εHf(t) = −1.0–8.2; TDMC = 2.09–1.62 Ga). Zircon O–Hf isotopic compositions of the metamafic and granitic rocks provide evidence for Mesoproterozoic (ca. 1.4 Ga) crustal growth and a substantial Palaeoproterozoic supracrustal component in the CTM. These findings and previous studies, reporting ca. 1.4 Ga magmatic rocks from other microcontinents of the CAOB, suggest that a large belt of Mesoproterozoic (ca. 1.4 Ga) juvenile continental crust formed in a continental terrane, fragments of which now occur over a distance of more than a thousand kilometres in the southern CAOB.<br
Keywords: Geochemistry; Petrology; Precambrian geology

Two phases of post-onset collision adakitic magmatism in the southern Lhasa subterrane, Tibet, and their tectonic implications - Lu, Tianyu; He, Zhen-Yu; Klemd, Reiner (Geological Society of America Bulletin, 2020)
Abundant Neogene adakitic magmatism occurred in the southern Lhasa subterrane after the onset of the India-Asia collision while convergence continued. However, the tectonic setting and magmatic evolution of the adakitic rocks are still under discussion. This study includes new mineral chemical and whole-rock geochemical data as well as zircon U-Pb and Lu-Hf isotopes of adakitic intrusive rocks from the Gyaca and Nyemo locations in the southern Lhasa subterrane. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) zircon U-Pb dating yielded crystallization ages of ca. 30 Ma for the Gyaca and Nyemo monzogranite and ca. 15 Ma for the Nyemo granodiorite. Both have common chemical signatures such as low MgO and heavy rare earth element contents as well as low compatible element abundances, indicating that these rocks result from partial melting of thickened lower crust with residual eclogite and garnet amphibolite. Furthermore, these rocks are characterized by variable positive zircon εHf(t) values, suggesting a juvenile magma source with variable ancient crustal contributions. Taking previous data into account, the adakitic magmatism concurs with an early late Eocene to Oligocene (ca. 38-25 Ma) and a late Miocene (ca. 20-10 Ma) phase. The adakitic rocks of the two phases are characterized by different fractionation evolutions of light and medium rare earth elements. We propose that the early-phase adakitic rocks were generated by the anatexis of Lhasa terrane lower crust owing to crustal shortening and thickening subsequent to the onset of the India-Asia collision and the upwelling of hot asthenosphere beneath the Lhasa terrane caused by the break-off of the Neo-Tethyan oceanic slab. The latest phase of adakitic rocks, however, relates to upwelling asthenosphere following the delamination and/or break-off of the subducting Indian continental slab.
CRIS-Team Scopus Importer:2020-08-07